2012
DOI: 10.1016/j.freeradbiomed.2012.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Proline dehydrogenase is essential for proline protection against hydrogen peroxide-induced cell death

Abstract: Proline metabolism has an underlying role in apoptotic signaling that impacts tumorigenesis. Proline is oxidized to glutamate in the mitochondria with the rate limiting step catalyzed by proline dehydrogenase (PRODH). PRODH expression is inducible by p53 leading to increased proline oxidation, reactive oxygen species (ROS) formation, and induction of apoptosis. Paradoxical to its role in apoptosis, proline also protects cells against oxidative stress. Here we explore the mechanism of proline protection against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
107
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 120 publications
(113 citation statements)
references
References 56 publications
(76 reference statements)
5
107
0
1
Order By: Relevance
“…Proline is a multifaceted amino acid with important roles in carbon and nitrogen metabolism; protein synthesis; and protection against various environmental factors such as drought (44), metal toxicity (45,46), osmotic stress (24,25), ultraviolent irradiation (47), unfolded protein stress (26,48), and oxidative stress (19,23,27,28,49). In this study, we explored the role of proline metabolism in oxidative stress protection by characterizing the oxidative stress response of wild-type and putA mutant E. coli strains.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Proline is a multifaceted amino acid with important roles in carbon and nitrogen metabolism; protein synthesis; and protection against various environmental factors such as drought (44), metal toxicity (45,46), osmotic stress (24,25), ultraviolent irradiation (47), unfolded protein stress (26,48), and oxidative stress (19,23,27,28,49). In this study, we explored the role of proline metabolism in oxidative stress protection by characterizing the oxidative stress response of wild-type and putA mutant E. coli strains.…”
Section: Discussionmentioning
confidence: 99%
“…Proline is a well-known osmoprotectant (24,25), and in E. coli, proline has been described as being a thermoprotectant by diminishing protein aggregation during heat stress (26). Proline has also been found to help combat oxidative stress, a property which has been explored in eukaryotes such as fungi, plants, and animals (19,20,27,28). The mechanism by which proline protects against oxidative stress appears to involve protection of intracellular redox homeostasis and, in the fungal pathogen Colletotrichum trifolii, upregulation of catalase (27).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Now, numerous laboratories have shown that the imino acid proline impacts a wide range of cellular processes, including bioenergetics, differentiation, growth, lifespan, and apoptosis (30, 70,74,75,84,95,97,99,153). It is well established that proline metabolism leads to increased mitochondrial reactive oxygen species (ROS) production via the electron transport chain (ETC) and that proline metabolism impacts cell survival and cell death in different species (14,30,84,97).…”
Section: Introductionmentioning
confidence: 99%